Vadba za razvoj vzdržljivosti otrok - Pančur, Neva (Šport (Ljubljana), 2019)
The article presents endurance training for children in the prepuberty stage. On the basis of general technical facts we wanted to present a specific example of endurance training in this stage, which is suitable for all sport disciplines. We have showed a systematic approach towards the development of this physical ability, regardless of the fact whether it is an indoor sport or an outdoor endurance sport. Another important thing is the awareness of the professionals working in sport about the main characteristics of training in this developmental stage. It is crucial to take into account the biological characteristics of children and didactic characteristics of endurance training.
Keywords: children; endurance; igra; otroci; play; sport; šport; vadba; vzdržljivost